Biological control of gray mold and Myrothecium leaf spot in begonias - Fujinawa, Miriam Fumiko; Pontes, Nadson de Carvalho; Borel, Filipe Constantino; Halfeld-Vieira, Bernardo de Almeida; de Goes, Antonio [UNESP]; Morandi, Marcelo Augusto Boechat (Elsevier, 2020)
The objective of this study was to evaluate the antagonism of Clonostachys rosea LQC62 and Trichoderma asperellum LQC96 against Botrytis cinerea and Myrothecium roridum, and to evaluate the application of these antagonists in the management of the diseases caused by these pathogens in commercial cultivation. Under controlled in vitro conditions, the production of soluble and volatile compounds was evaluated along with parasitism in paired cultures, competition by colonization in begonia leaf discs, and the effect of the application of the antagonists in the control of gray mold and Myrothecium leaf spot in the commercial cultivation of begonia. Both LQC62 and LQC96 produced soluble compounds in a culture medium that were capable of inhibiting the development of B. cinerea, which was not observed for M. roridum. Both antagonists produced volatile compounds that led to a reduction in the development of the pathogens. There was an overlap of the colonies of the antagonists with those of the pathogens, indicating hyper-parasitic activity. The antagonists colonized the begonia leaf discs, and the application of these antagonists prior to inoculation promoted a reduction in the sporulation of the pathogens of up to 100%. Weekly foliar sprays of LQC62 reduced the incidence of gray mold and of Myrothecium leaf spot in commercial cultivation.
Keywords: Begonia elatior; Botrytis cinerea; Clonostachys rosea; Myrothecium roridum; Trichoderma asperellum